2012
DOI: 10.1080/01904167.2012.631668
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular and Molecular Distribution of Cadmium in Two Rice Genotypes With Different Levels of Cadmium Accumulation

Abstract: The chemical form and subcellular and molecular distribution of cadmium (Cd) in the roots and leaves was investigated in two rice genotypes: the low Cd-accumulating "GuangyuanzhanNo. 3', and the high Cd-accumulating "Zhenguiai." Elevated Cd level in the medium caused a significant increase in Cd concentration in all parts of the roots and leaves. The soluble fractions in leaves and roots of 'Zhenguiai' contained a higher proportion of the Cd than those in 'Guangyuanzhan No. 3'. Furthermore, 'Zhenguiai' had a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 34 publications
2
8
0
1
Order By: Relevance
“…This result is consistent with the observation that D62B absorbs more Cd than D83B. Investigation on several rice genotypes in solution cultivations revealed that a larger cell wall fraction of Cd in the roots was associated with lower translocation ratios from the roots to the aboveground parts (Liu et al 2014;Yu et al 2012). Our results were generally in agreement with their results.…”
Section: Adsorption Chelation Compartmentalization and Translocasupporting
confidence: 95%
“…This result is consistent with the observation that D62B absorbs more Cd than D83B. Investigation on several rice genotypes in solution cultivations revealed that a larger cell wall fraction of Cd in the roots was associated with lower translocation ratios from the roots to the aboveground parts (Liu et al 2014;Yu et al 2012). Our results were generally in agreement with their results.…”
Section: Adsorption Chelation Compartmentalization and Translocasupporting
confidence: 95%
“…Former studies on Cd subcellular distribution and translocation were conducted with two rice cultivars in solution cultivations, and the results indicated that larger ratios of Cd in the soluble fraction in the roots were associated with higher ratios of Cd distribution from the roots to the shoots Yu et al 2012). Our results on the relation between Pb subcellular distribution in root and its translocation from root to shoot were generally in agreement with their results on Cd.…”
Section: Variations Among Rice Cultivars In Pb Subcellular Distributisupporting
confidence: 88%
“…Cd–O storage forms have been also interpreted as Cd in the apoplast that binds to cell wall components ( Isaure et al, 2015 ). Extraction-based analysis of Cd compartmentalization in rice shoots revealed that large fractions of Cd in the shoot (>40%) are located in the apoplast ( Yu et al, 2012 ; Siebers et al, 2013 ; Zhang et al, 2014 ). This Cd accumulation in the apoplast may derive from inefficient loading of Cd from the xylem into the symplast in the shoot ( Olsen and Palmgren, 2014 ) that requires membrane influx transporters that are not identified yet ( Wang W. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This recycling step includes an organized degradation of organelles and organic compounds, including proteins. Significant fractions of Cd can be present in organelles in rice shoots (5–17%, Yu et al, 2012 ; Siebers et al, 2013 ; Zhang et al, 2014 ) and/or replacing nutrients such as Zn in proteins in plants ( Tang et al, 2014 ). Hence, in our study, the Cd that was bound to S in the shoots at flowering could have been remobilized toward the grains during grain filling ( Kashiwagi et al, 2009 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%